Immune parameters as biomarkers of Mycobacterium tuberculosis sterilization during anti-tuberculosis treatment - Djoba Siawaya, Joel Fleury (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2008.